2015
DOI: 10.1162/jocn_a_00690
|View full text |Cite
|
Sign up to set email alerts
|

Predicting the Semantic Category of Internally Generated Words from Neuromagnetic Recordings

Abstract: Abstract■ In this study, we explore the possibility to predict the semantic category of words from brain signals in a free word generation task. Participants produced single words from different semantic categories in a modified semantic fluency task. A Bayesian logistic regression classifier was trained to predict the semantic category of words from single-trial MEG data. Significant classification accuracies were achieved using sensorlevel MEG time series at the time interval of conceptual preparation. Seman… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
9
0

Year Published

2016
2016
2022
2022

Publication Types

Select...
6
2

Relationship

1
7

Authors

Journals

citations
Cited by 13 publications
(9 citation statements)
references
References 55 publications
(75 reference statements)
0
9
0
Order By: Relevance
“…One reason for the prior gap is a heavy focus on concrete object knowledge (see Martin 2007 for a review). Past findings have identified neural areas that respond more strongly to 1 category of object than another ( Martin et al 1996 ; Chao and Martin 2000 ; Anzellotti et al 2011 ; Konkle and Caramazza 2013 ) or that contain pattern information about individual object kinds ( Haxby et al 2001 ; Kriegeskorte et al 2008 ) and which do so across modalities of stimulus presentation ( Simanova et al 2013 ; Devereux et al 2013 ; Fairhall and Caramazza 2013 ; Fairhall et al 2013 ; Clarke and Tyler 2014 ). However, these approaches are not sufficient to identify semantic representations per se, because concepts referring to concrete categories point to both semantic and sensory knowledge: concepts like “banana” are inevitably associated with specific, sensory qualities, such as the color yellow.…”
Section: Introductionmentioning
confidence: 99%
“…One reason for the prior gap is a heavy focus on concrete object knowledge (see Martin 2007 for a review). Past findings have identified neural areas that respond more strongly to 1 category of object than another ( Martin et al 1996 ; Chao and Martin 2000 ; Anzellotti et al 2011 ; Konkle and Caramazza 2013 ) or that contain pattern information about individual object kinds ( Haxby et al 2001 ; Kriegeskorte et al 2008 ) and which do so across modalities of stimulus presentation ( Simanova et al 2013 ; Devereux et al 2013 ; Fairhall and Caramazza 2013 ; Fairhall et al 2013 ; Clarke and Tyler 2014 ). However, these approaches are not sufficient to identify semantic representations per se, because concepts referring to concrete categories point to both semantic and sensory knowledge: concepts like “banana” are inevitably associated with specific, sensory qualities, such as the color yellow.…”
Section: Introductionmentioning
confidence: 99%
“…A typical constraint is to minimize the source power. Among these methods, the Minimum Norm Estimate (MNE) relies on minimizing the L2-norm and is one of the most widely used techniques [ 4 , 7 , 8 , 18 37 ]. By contrast, estimates obtained by minimizing the L1-norm are referred to as Minimum-Current Estimates (MCE) [ 34 , 38 ].…”
Section: Introductionmentioning
confidence: 99%
“…The question is, whether MVPA is sensitive to internally generated, behaviourally relevant information, even with interfering material driving the neural response. While decoding of semantic category membership has been shown in the absence of a stimulus on screen (Simanova et al [2015]), this was only shown for single words. To our knowledge there are no language studies explicitly probing reactivation in sentence context through MVPA.…”
Section: Discussionmentioning
confidence: 99%